General, Applied and Systems Toxicology 2009
DOI: 10.1002/9780470744307.gat001
|View full text |Cite
|
Sign up to set email alerts
|

Basic Elements of Toxicology

Abstract: Toxicology is a multidisciplinary science concerned with determining the potential of chemicals and certain physical agents, such as ionizing radiation, to produced adverse effects in living organisms. Adverse effects in the context of this definition are those that are detrimental to the normal functioning or survival of the organism. If such effects occur, it is necessary to know their nature, incidence, mechanism of production, factors influencing their development and reversibility. This overview chapter d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 208 publications
(177 reference statements)
0
13
0
3
Order By: Relevance
“…According to the toxicity classification by Ballantyne et al ( 15 ), umbelliprenin showed potentially toxic effects against the HT29, CT26, MCF-7, 4T1, A172, and GL26 cancer cell lines at all three incubation times. As depicted in Figure 1 , umbelliprenin inhibited expansion of these cells in a concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 97%
“…According to the toxicity classification by Ballantyne et al ( 15 ), umbelliprenin showed potentially toxic effects against the HT29, CT26, MCF-7, 4T1, A172, and GL26 cancer cell lines at all three incubation times. As depicted in Figure 1 , umbelliprenin inhibited expansion of these cells in a concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 97%
“…Toxicity test results were analyzed by the LC 50 computer program (Trimmed Spearman-Karber Method, Version 1.5) so as to calculate LC 50 values and 95% confidence intervals [31] ( Table 3). After evaluating MIC and LC 50 values of the compounds (5a-5i) together, the 5a, 5c, and 5d (LC 50 > 1000 mg/mL) were determined as non-toxic.…”
Section: Microbiologymentioning
confidence: 99%
“…The fundamental purpose of toxicological evaluation is to uncover substances that possess properties, rendering them a potential hazard to human health. 1 However, the identification of such substances is often meaningless unless the strength of that hazard, often termed potency, is also characterized. With respect to the toxicological hazard known as skin sensitization, the simple identification of hazard has been ensured for many decades, and the key details were well documented.…”
mentioning
confidence: 99%